Overcoming Resistance in Relapsed Anaplastic Large-Cell Lymphoma, ALK-Positive (Literature Review and Clinical Experience) - YuE Vinogradova; NG Chernova (Клиническая онкогематология)

(untitled)
Peripheral T-cell lymphomas (PTCL) are characterized by unfavorable prognosis and poorer survival in comparison with B-cell lymphomas. Probability of remission on first-line PTCL therapy is not higher than 60 % with high relapse rate. Long-term remission in PTCL relapses/progression cases typically fails to be achieved. The present article provides literature review and the authors’ own clinical experience in the management of anaplastic large-cell lymphoma, ALK-positive with primary skin and soft tissue lesions in an 65-year old female patient. After NHL-BFM-90 intensive chemotherapy the first 5,5-year complete remission was achieved in this patient. Afterwards a СНОР therapy-resistant relapse was identified. Chemotherapy-resistance of tumor was successfully overcome by adding of epigenetic drugs to cytostatic antitumor therapy. The duration of second complete remission is 3 years. Oncohematological diseases with either initial chemotherapy-resistance or the resistance acquired during antitumor therapy are most efficiently treated by various drug combinations including monoclonal antibodies, epigenetic drugs, and cytostatic therapy.